Efektivitas Intervensi Mindfulness Bonding Ibu dan Janin Menggunakan Smartphone Terhadap Kecemasan Ibu Hamil Menjelang Persalinan - Indah Adilla; Misrawati Misrawati; Ganis Indriati (LPPM Hang Tuah Pekanbaru, 2023)
Anxiety before childbirth is the main psychological problem experienced by pregnant women. Mindfulness bonding between mother and fetus is a technique that can increase the emotional bond between mother and fetus so as to reduce anxiety. The implementation of this mindfulness bonding intervention for mother and fetus can be done using a smartphone so that it can be accessed without the time and place limits. This study aims to analyze the effectiveness of the mindfulness bonding intervention of mother and fetus using a smartphone on the anxiety of pregnant women before delivery. The study used a quasi-experimental design with a pre and post-test design with a control group. The sample of this research was 34 pregnant women before delivery, divided into two groups, namely 17 respondents of pregnant women in the experimental group and 17 pregnant women in the control group by using a purposive sampling technique. Data was collected using the PRAQ-R2 questionnaire and the MIESRA application with data analysis using a t-test. There was a significant change before and after being given the mindfulness bonding intervention of mother and fetus using a smartphone on the anxiety of pregnant women before delivery (p-value = 0.001). The mindfulness bonding intervention of mother and fetus using a smartphone with the MIESRA application is effective in reducing the anxiety level of pregnant women before delivery.